The Legal Instruments for Regulating Transregional Cooperation: The Experience and Trends of the Contemporary European Union - Scherbak, Viktor; Tretiak, Oleksii; Kliachyn, Andrii; Batrymenko, Oleh; Kadolonok, Ivan (Jurnal Cita Hukum, 2025)
The subject of the study is optimal models of legal regulation of transregional cooperation, which is an essential task from the point of view of new ways of realising national interests in international relations. The article aims to establish the peculiarities of the legal regulation of transregional cooperation, taking into account the experience of the EU. The study results showed that legal instruments can be bilateral or multilateral and define each party’s obligations and rights within the cooperation framework. The differences in the legal systems of the participating countries may make the application and enforcement of agreements difficult. The aspiration to intensify integration and interaction between countries and regions is substantiated. Practical transregional cooperation can promote trade and economic growth, strengthen democratic institutions, protect human rights, and address shared challenges such as climate change and migration. The ability to fund projects to support civil society, human rights, and the rule of law, as well as strengthen democratic institutions in neighbouring countries, contributes to stability and development at the regional level. In addition, practical cross-border cooperation between the EU and its neighbouring countries requires a comprehensive approach. The role of EU cooperation with African countries must be adapted to each region’s specific needs and characteristics. The standards of most successful models of transregional cooperation should be recognised as the models of cross-border cooperation of states located on the eastern and southern borders of the single European space.